2020
DOI: 10.3390/cells9040992
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Driven Immune Escape in the Tumor Microenvironment

Abstract: The tumor microenvironment is a complex ecosystem comprised of many different cell types, abnormal vasculature and immunosuppressive cytokines. The irregular growth kinetics with which tumors grow leads to increased oxygen consumption and, in turn, hypoxic conditions. Hypoxia has been associated with poor clinical outcome, increased tumor heterogeneity, emergence of resistant clones and evasion of immune detection. Additionally, hypoxia-driven cell death pathways have traditionally been thought of as tolerogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
161
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(162 citation statements)
references
References 148 publications
(168 reference statements)
1
161
0
Order By: Relevance
“…These findings suggested that SHMT2, the high expression of which can slow down the process of glycolysis and augment the ratio of lactate and pyruvate, plays a vital role in the transition of PKM2, resulting in the glycolytic metabolic shift ( 10 , 15 , 34 ). It is known that one of the OSCC microenvironment features is hypoxia and that normal epithelial cells cannot adjust at poor oxygen pressure, so a high expression of SHMT2 may promote tumor cell survival for a long time in the OSCC microenvironment ( 9 ). Moreover, it is exactly that SHMT2 in mitochondria, not SHMT1 in the cytoplasm, was expressed highly in rapidly proliferating cancer cells ( 31 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that SHMT2, the high expression of which can slow down the process of glycolysis and augment the ratio of lactate and pyruvate, plays a vital role in the transition of PKM2, resulting in the glycolytic metabolic shift ( 10 , 15 , 34 ). It is known that one of the OSCC microenvironment features is hypoxia and that normal epithelial cells cannot adjust at poor oxygen pressure, so a high expression of SHMT2 may promote tumor cell survival for a long time in the OSCC microenvironment ( 9 ). Moreover, it is exactly that SHMT2 in mitochondria, not SHMT1 in the cytoplasm, was expressed highly in rapidly proliferating cancer cells ( 31 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the tumor microenvironment under hypoxia promotes immune escape and hypoxia in the OSCC microenvironment, indicating poor prognosis and reflecting the involvement of the metabolic activity in mitochondria ( 9 ). Since the Warburg effect was discovered to be associated with tumor progression, increasing numbers of scholars have investigated energy metabolism in the tumor microenvironment ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of glycolytic metabolites and the expression of cytokines and chemokines (e.g., CCL5, CXCL12, and CXCR4) driven by HIF-1α also generate an unfavorable scenario for immune cell recruitment. Indeed, an oxygen-deprived tumor microenvironment influences the migration and activity of both innate and adaptive immune cells [ 69 ].…”
Section: Impact Of Metabolic Reprogramming Driven-hypoxia On Tumormentioning
confidence: 99%
“…Hypoxia has been known to play a role in the progression of cancer cells by suppressing the response of the immune system and by altering the differentiation of immune cells [ 81 ], and hypoxic sEVs are involved in mediating those effects. For example, miR-10 and miR-21 secreted by hypoxic sEVs derived from glioma cells target RAR-related Orphan Receptor α (Rorα) and PTEN expression, respectively, in order to repress the myeloid-derived suppressor cells [ 65 ].…”
Section: Hypoxic Sevs’ Cargo and Its Role In Key Biological Procesmentioning
confidence: 99%
“…Natural killer (NK) cells are innate lymphoid cells, which have a strong anti-tumor activity [ 81 ]. NK cell function is impaired under hypoxia, which induces a decrease of the expression of several NK cell receptors responsible for the killing of target cells [ 81 , 86 ]. Berchem et al have shown that the transfer of hypoxic tumor sEVs carrying TGF-β and miR-23a has immunosuppressive effects on NK-cells [ 48 ].…”
Section: Hypoxic Sevs’ Cargo and Its Role In Key Biological Procesmentioning
confidence: 99%